Elaboración del manual de procesos del área de campismo y recreación del laboratorio de interpretación turística para la carrera de ingeniería en ecoturismo de la UA-CAREN de la Universidad Técnica de Cotopaxi - Pérez Llumitasig, Edwin Patricio (2014)
The present research consists in the Elaboration of the Manual process in the camping and recreation area, its contents shows the objective consolidation for development of the manual, identifying the necessary process to the good working the components in area of study. It performed a previous research in order to identify the necessary requirements, the information contains an elaborated report which It took bibliography review ,descriptive and field research, analytical, synthetic methods, primary, secondary source, and as technique the theoretical base interview. The research contains three chapters, chapter 1 contains for the development of the Manual process in the camping and recreation area content is maintained in the thegoretical base through an technical analysis, chapter 2 identifies the methodological proposal , through general way and examples of each one to integrate the Manual through methodologic....